PENGARUH E-CRM DAN E-WOM TERHADAP LOYALITAS DIMEDIASI KEPUASAN PELANGGAN RS PDS TANGSEL - Rama Al Mizan (2023)
The Effect of e-CRM and e-WOM on Loyalty mediated by Customer Satisfaction (Study at PDS Hospital in South Tangerang) By Rama Al Mizan Abstract This study uses a quantitative method with the aim of proving the influence of e-CRM and e-WOM on loyalty mediated by customer satisfaction (study at PDS Hospital in South Tangerang). This study used 101 respondents from PDS Hospital patients as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) There is a direct and significant influence between e-CRM to Loyalty. (2) There is no direct and significant effect between e-WOM to loyalty. (3) There is a direct and significant influence between e-CRM To Loyalty which is mediated by Customer Satisfaction?. (4) There is a direct and significant influence between e-WOM To Loyalty which is mediated by Customer Satisfaction? Keywords: e-CRM, e-WOM, Loyalty, Customer Satisfaction